Le projet de désalinisation à Lima : des enjeux territoriaux à la transition socio-technique du secteur de l’eau - Fanny Bertossi; Jérémy Robert (Développement Durable et Territoires)
In 2013, the Peruvian government announced the first seawater desalination project for public urban water service in Lima (Perú). The article looks to analyze the decision-making process that led to the adoption of the infrastructure project. The infrastructure is presented as an innovation in the national context where large Andean hydraulic infrastructures are destabilized. We analyze the convergence of multiple interests that contribute to trigger a sociotechnical transition in the water sector. This analysis allows us to underline the mutual impact between solutions for water production and management and urban development trends, especially around territorial and agency issues.